TEACHING ENGLISH AS A SECOND LANGUAGE (ESL) (American Journal of Interdisciplinary Research and Development, 2024)
This article about teaching English as a Second language. It has given many advices, approaches, and some learning platforms which are useful for teachers who work as foreign languages teacher. Moreover, it includes some information about assessments for ESL. There is exist some barriers in learning languages.